Sistem Informasi Pembayaran Tambahan Penghasilan Berdasarkan Beban Kerja Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Tanah Bumbu - Abdul Rozaq; Raden Kelik Hardinto; Annurrahman Annurrahman; Dewi Susanti (P3M Politeknik Negeri Banjarmasin, 2018)
Currently the financial administrators of the District Education and Culture Office of Tanah Bumbu do the work of input data paying additional income based on workload (TPBBK) using MsExcel so that the data input constraints are still manual and the database is not adequate so the work becomes ineffective and efficient. So this study aims to find the problems, design, build and implement the Information System Payments TPBBK the Office of Education and Culture Tanah Bumbu Regency. The research method used is applied research method (Applied Research). Data collection techniques used are observation and interview. Beginning with analyzing functional and non functional requirements and PIECES analysis. The results of this study are aimed primarily to facilitate financial admisnistrator in making reports TPBBK, produce reports TPBBK precisely and save time in the process.